Bir Kısır Döngü: Dünyada ve Türkiye'de Çocuk İşçiliği ve İşsizlik - Çöpoğlu, Mustafa (Muş Alparslan Üniversitesi, 2018)
Beingat the forefront field that must be intervened, child labor is importantbecause it negatively affects children's physical, psychological andsociological development. According to the International Labour Office's 2017data, 151.6 million children aged 5 to 17 years are working as child labourers.The cause of child labor is unemployment and also the poverty which is aconsequence of unemployment. According to The Child Labour Survey results thatwas made by the Turkey Statistical Institute in 2006; the leading working causeof the children between is "to contribute to the household income"with a percentage of 51.1%. Children, who have to work because of their family’sbad socio-economic situation, are involved in working life to provide incomerather than to learn a profession. In this study aiming to contribute to theelimination of the identified negative situations, the current situation ofchild labour in the world and in Turkey is going to be analysed and bymentioning national and international intervention methods to prevent childlabour, proposals for the development of policies will be presented.

Günümüzdemüdahale edilmesi gerekli alanların başında gelen çocuk işçiliği; çocuklarınfiziki, psikolojik, sosyolojik gelişimlerini olumsuz etkilemesi sebebiyleönemlidir. Uluslararası Çalışma Örgütü’nün 2017 verilerine göre, 5-17 yaşgrubundaki 151, 6 milyon çocuk, çalışmaktadır. Çocuk işçiliğinin sebebi işsizlikve işsizliğin bir sonucu olan yoksulluktur. Türkiye İstatistik Kurumu’nun 2006tarihli Çocuk İşgücü Anketi sonuçlarına göre, 6-17 yaş gurubundaki çocuklarınçalışma nedenlerinin başında % 51, 1 ile “hane halkı gelirine katkıda bulunmak”gelmektedir. Ailelerinin sosyo-ekonomik durumları kötü olduğu için çalışmakzorunda kalan çocuklar; çalışma hayatında meslek öğreniminden ziyade gelirsağlamak için yer almaktadırlar. Anılan olumsuzlukların giderilmesine katkısağlamayı amaçlayan bu çalışmada; çocuk işçiliğinin dünyada ve Türkiye’dekimevcut durumu analiz edilecek olup, çocuk işçiliğini önlemeye yönelik ulusal veuluslararası müdahale yöntemlerinden bahsedilerek politikalar geliştirilmesineyönelik öneriler sunulacaktır.
A Vicious Circle: Child Labor and Unemployment in the World and Turkey
anemon
Keywords: Child Labour; Working Children; Poverty; Combatting Child Labour; Çocuk İşçiliği; Çalışan Çocuklar; Yoksulluk; Çocuk İşçiliğiyle Mücadele